CONSUMER TRUST IN E-COMMERCE: THE EFFECT ONLINE REVIEWS AND RATINGS - Panjaitan, Feliks Anggia Binsar Kristian (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This study analyzes the influence of online reviews and ratings on consumer trust in e-commerce, with the aim of identifying the key factors that influence this dynamic. Using a Systematic Literature Review approach, this study examines relevant studies to explore the role of positive, negative reviews, and elements such as reviewer credibility in shaping consumer trust. The results show that the quality and authenticity of reviews have a significant impact on consumer trust, which has implications for better review management strategies for e-commerce platforms.